Perbaikan Kemampuan Pemecahan Masalah Matematika melalui Model Pembelajaran Kooperatif Tipe STAD - Aswin Saputra; Endaryono Endaryono (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2020)
The purpose of this research is to find out the improvement of students' mathematical problem solving skills in class III through the STAD type cooperative learning model at SDN Kapuk Muara 01. The method used in this study is an experimental approach with classroom action research techniques, which is an action taken by teachers and researchers to improve teaching by making changes and learning the effects of those changes. The technique used in data collection is the end of the cycle test and observation. The results showed that the Mathematics learning process by applying the STAD type cooperative model was able to improve students' mastery of concepts for the better. The results obtained in the first cycle of absorption is 51,163%, then improved in the second cycle with the results of the absorption of the class is 90.69%. This shows the progress where students have gotten good learning outcomes from cycle I.